The Influence of Education on Improving Adolescent Girls' Knowledge Regarding Anemia in the Gembong Public Health Center Area - Khatimah, Gita Khusnul; Destra, Edwin (Indonesian Scientific Publication, 2023)
existence of a problem by systematically collecting data within a community. Anemia is a health issue that commonly arises, characterized by a condition in which the body's hemoglobin levels fall below the normal range. According to the 2018 Riskesdas data, the prevalence of anemia among adolescent girls reaches approximately 32%, meaning that 3 to 4 out of every 10 adolescent girls experience anemia. Anemia in adolescent girls has the potential to result in various negative consequences, such as reduced immunity, decreased academic performance, and diminished productivity. These observations emphasize the necessity of conducting a community diagnosis to enhance awareness and reduce cases of anemia among adolescent girls in the Puskesmas Gembong working area. The primary objectives include improving knowledge about anemia and decreasing the number of anemia cases among adolescent girls in the Puskesmas Gembong working area. An intervention plan in the form of educational sessions about anemia was developed. Following the intervention, there was an improvement in knowledge, with post-test scores exceeding 60% for over 50% of the participants. Therefore, this community diagnosis serves to enhance knowledge about anemia among adolescent girls and has resulted in the identification of anemia cases among them, leading to appropriate referrals for treatment.